DEVELOPMENT OF CONTEXTUAL-BASED MODULES ON LINES AND ANGLES FOR SEVENTH GRADE STUDENTS AT SMP NEGERI 1 ULUSUSUA - Laia, Yunuli (Universitas Nias Raya, 2024)
This research aims to develop a module focused on lines and angles to enhance students' contextual skills. The study employs a Research and Development (R&D) approach using the 4D model (define, design, development, disseminate), with data collected through validation, questionnaires, and tests, analyzed both qualitatively and quantitatively. Based on the findings, the lines and angles module is proven to be valid, practical, and effective. Subject matter experts rated it as valid (75%), media experts also rated it valid (74.07%), and language experts rated it as very valid (75%). In limited class trials, practicality was rated very high (average 4.57), and similarly high in field trials (average 4.43). Effectiveness in improving learning outcomes was moderately good in limited class trials (average 0.65) and field trials (average 0.68). The developed module is intended to support independent learning among students and assist teachers in effectively teaching mathematics.